Findbuch des Bestandes Abt. 49. Schleswig-Holsteinische Regierung auf Gottorf 1834-1851 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2017)
Since 1648 and 1713, the government chancellery in Glückstadt for Holstein and the higher court in Gottorf for Schleswig formed the highest sovereign authorities in the duchies below the central administrative bodies in Copenhagen. In 1834 the separation of the justicial and the administrative authority took place at the middle level. A new administrative authority was established under the name "Schleswig-Holstein Government" (also known as Provincial government). When it was set up, the Schleswig-Holstein government took over parts of the Governorship's archives, as well as the majority of the administrative acts of the Gottorf Higher Court and the government chancellery in Glückstadt. The government left most of this writing untouched; only a small part of it was being continued. In order to facilitate the use of the important and thematically rich Dept. (Abt.) 49, the collection was completely reviewed in 2012/2013 and included in the archive database "AIDA". In this process, the information on the old means of finding the titles and terms of all archival material in the stock was checked.